GrumPy: an automated approach to simplify issue data analysis for newcomers - Mota Jr., Joselito; Santana, Railana; Machado, Ivan (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
The development model of open-source projects involves intensive developers’ collaborations to develop new features and maintain existing ones. Repositories hosting the projects may offer communication facilities to make partnerships happen in practice systematically. Issue reporting is one of the most employed strategies, as it carries valuable information about the software behavior or the repository itself. Indeed, issues have become the focus of several recent investigations, leading to an increased demand for automated approaches to support issue mining and analysis. The literature has brought a set of solutions for automating issue mining and analysis. However, they do not often provide developers with a user-friendly interface or an easy way to mine, manage or visualize issues’ data. Therefore, this paper introduces GrumPy, an open-source environment aimed to provide an automated approach to mine, manage, and visualize statistics about reported issues from open-source repositories. It provides a manageable multi-miner, a module to handle or visualize issues’ components, and a dashboard module responsible for showing repository data graphically. Our tool goal is to facilitate issues research work and its components.